2010
DOI: 10.1007/s00540-010-0942-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-rich saline solution attenuates renal ischemia–reperfusion injury

Abstract: Purpose Renal ischemia-reperfusion (I/R), an important cause of acute kidney injury, is unavoidable during various types of operations, including renal transplantation, surgical revascularization of the renal artery, partial nephrectomy, and treatment of suprarenal aortic aneurysms. Exacerbation of I/R injury is mediated by reactive oxygen species (ROS). A recent study has shown that hydrogen has antioxidant properties. In this study, we tested the hypothesis that a hydrogen-rich saline solution (HRSS) attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 24 publications
3
41
0
Order By: Relevance
“…Our present study found that intraperitoneal injection of hydrogen-rich saline significantly attenuated I/R-induced apoptosis, MPO activity, MDA, 8-OhdG, TNF-a, IL-1b, and IL-6 levels and increased SOD and CAT activities in the renal tissues compared with those in I/R plus physiologic saline treatment rats, which was in consistent with a recent study that demonstrated a decrease in the serum level of 8-OhdG after continuous intravenous administration of hydrogen-rich saline [9].…”
Section: Discussionsupporting
confidence: 93%
“…Our present study found that intraperitoneal injection of hydrogen-rich saline significantly attenuated I/R-induced apoptosis, MPO activity, MDA, 8-OhdG, TNF-a, IL-1b, and IL-6 levels and increased SOD and CAT activities in the renal tissues compared with those in I/R plus physiologic saline treatment rats, which was in consistent with a recent study that demonstrated a decrease in the serum level of 8-OhdG after continuous intravenous administration of hydrogen-rich saline [9].…”
Section: Discussionsupporting
confidence: 93%
“…Renal ischemia/reperfusion (I/R) is a significant cause of acute kidney injury (AKI) and an inevitable consequence of several operations, including the treatment of suprarenal aortic aneurysms, partial nephrectomy, surgical revascularization of the renal artery and renal transplantation [1]. Renal ischemia-reperfusion injury (IRI) is clearly a leading clinical problem in native kidneys as well as in the setting of renal transplantation, but the pathogenesis of renal IRI remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Renal ischemia/reperfusion (I/R) injuries are the major causes of acute renal failure and may be involved in the development and progression of certain forms of chronic kidney disease (1). Ischemia is associated with oxidative stress and apoptosis.…”
Section: Introductionmentioning
confidence: 99%